Strong and chemically inert sinter crystallised glass ceramics based on Estonian oil shale ash. (February 2014) - Marangoni, M.; Ponsot, I.; Kuusik, R.; Bernardo, E.
Abstract : In heat and power production, oil shale combustion forms substantial amounts of solid waste, including fly ash. The present paper is dedicated to the manufacturing of frit derived glass ceramics from melting high amounts of this waste (65–67 wt-%) combined with inexpensive minerals, such as rhyolite (33–35 wt-%). Owing to a surface mechanism of crystallisation, fine powders led to glass ceramics with high strength and reliability, even for rapid treatments (fast heating, at a rate of 40°C min −1, followed by 30 min holding stage). To minimise the presence of pressing and demoulding induced defects, the tiles were prepared by incorporating binders, i.e. polyethylene glycol or kaolin, to the frit mixtures. Finally, the stabilising effect of recycled borosilicate glass powders, mixed with waste derived glass powders, was also investigated with promising results for the production of a chemically stable material.